E-commerce 10% Strategy on COD Orders: Enhancing Your Shopping Experience (Global Journal of Management and Business Research, 2024)
ln the dynamic landscape of online shopping, the groundbreaking "10% Strategy on COD Orders" emerges as a transformative force, orchestrating a subtle yet powerful shift in the conventional e-commerce paradigm. This innovative strategy mandates a strategic 10% advance payment at the point of purchase, introducing a multifaceted approach that transcends traditional norms and reshapes the landscape of online retail. Functioning as a financial sentinel, the strategy adeptly absorbs return costs and mitigates operational expenses, thereby creating a robust and resilient financial framework for e-commerce platforms. Beyond its monetary role, the 10% advance payment serves as a proactive measure, offsetting potential challenges associated with delivery issues when orders are declined, streamlining operations, and paving the way for a smoother and more adaptable operational landscape. From the consumer's standpoint, the strategy ensures a worry-free and transparent shopping journey, guaranteeing straightforward returns and enhancing the accessibility of customer support services. This research paper delves into the intricacies of the 10% Strategy on COD Orders, shedding light on its transformative influence on the financial dynamics and operational efficiency of e-commerce platforms. Utilizing primary data collection tools, the study explores consumer perceptions, experiences, and preferences, providing a comprehensive understanding of the strategy's implications.
Keywords: Groundbreaking; Paradigm; Sentinel; Earmarked; Multifaceted